Adjudication of Grievances in Public Service of Canada - Aggarwal, Arjun (Relations industrielles / Industrial Relations, 1973)
Employer-employee relations in the Federal Public Service of Canada entered a new era with the proclamation on March 13, 1967, of three Acts— The Public Service Staff Relations Act ; The Public Service Employment Act ; and anAct to Amend the Financial Administration Act. The employees have been guaranteed the right to organize, the right to bargain, the right to strike and the right to get grievances adjudicated by an independent tribunal. The statutory right to grieve and get the grievances adjudicated have provided to the federal public employees a sense of justice and « fairplay ». The adjudication system has made the private sector of industrial jurisprudence applicable to the federal public services with a remarkable success. This article deals with the function and operation of the statutory Grievance Process and Adjudication.